Consumer opinion of stair descent devices used during emergency evacuation from high-rise buildings. Issue 5 (3rd September 2021) - Hedman, Glenn; Mehta, Jay; Lavender, Steven; Reichelt, Paul; Conrad, Karen; Park, Sanghyun
ABSTRACT: The use of stair descent devices is an important part of a comprehensive emergency evacuation plan. To date, there is little research on consumer opinion of these devices. A pilot study was performed at a local center for independent living, enabling 14 consumers with mobility impairments to state their initial impressions of 14 devices, representing three general designs: carry-type, track-type, and sled-type. Consumers were able to view the devices, ask questions, and view short videos of the devices in use. Afterwards, consumers were given the opportunity to try out one or more of the devices, and provide their opinion after each trial run. Consumers provided feedback on specific design features, how they anticipated they would feel about using each, and whether they considered each device acceptable for use. Trial use enabled more in-depth opinions, and in some cases, a change in opinion on acceptability.